The Influential Factors of Parents' Involvement in Early Childhood Education: Study of Children 4-6 Years Old - Sartika Kale; Sugito -; Septinda Rima Dewanti (Universitas Trunojoyo Madura, 2023)
This research aimed at identifying the influence of socio-economic status towards parents’ involvement, the influence of teacher social competence towards parents’ involvement, the influence of school climate towards parents’ involvement, and the influence of parents’ socio-economic status, teacher social competence, and school climate towards students’ involvement in early childhood education, specifically in kindergartens located in Kupang City, East Nusa Tenggara. This quantitative study was designed using ex post facto reseach method. There were 203 parents of 89 Kindergartens chosen to be the research sample determined by using purposive sampling technique. Questionnaires were used to collect the data which was then analyzed using descriptive analysis and regression. The result of study reveals a significant influence of soci-economic status; no significant influence of teacher social competence towards parents’ involvement; a significant influence of school climate towards parents’ involvement; and a simultaneously significant influence of socio-economic status, teacher social competence, and school climate towards parents’ involvement. Finally, in order to improve parental involvement, education policymakers have to consider socioeconomic status and school climate.